Analysis of Determinants of Tourist Visits to Ecotourism Objects in East Barito Regency - Hermannus Kleden (Journal Magister Ilmu Ekonomi Universtas Palangka Raya : GROWTH, 2022)
This study aims: 1) To determine the effect of Tourist Attractions on Tourist Visits to Ecotourism Objects in East Barito Regency, 2) To determine the effect of Services on Tourist Visits to Ecotourism Objects in East Barito Regency, 3) To determine the effect of Facilities on Tourist Visits to Ecotourism Objects East Barito Regency, 4) To find out the effect of Price on Tourist Visits to Ecotourism Objects in East Barito Regency. The research design is descriptive quantitative research. Data collection techniques using a questionnaire. Test the data analysis prerequisites using Multiple Linear Regression Analysis. The results of this study indicate that the price variable has no and significant effect on Tourist Visits to Ecotourism Objects in East Barito Regency, while the variables of Tourist Attraction, Services and Facilities indicate a positive and significant influence on Tourist Visits to Ecotourism Objects in East Barito Regency